Social Responsibility in SMEs: A Bibliometric Analysis - Fadrian Dwiki Maulanda; Gatot Yudoko; Bambang Rudito (International Journal of Entrepreneurship and Sustainability Studies, 2023)
By adopting a bibliometric analysis approach, this study systematically reviews and retrospectively analyzes the rapidly emerging literature on Corporate social responsibility in Small and medium-sized enterprise (SME). The analysis reveals the intellectual structure of papers that have been published from 2000 to 2022 on the Scopus database. Based on the research conducted, the number of articles on CSR in SMEs is increasing, indicating a need for research in CSR practices and recognizing SMEs' role in sustainable development. The UK, Spain, and Italy show high commitment to SDGs, while research on CSR in SMEs is limited in Eastern Europe and Africa. The cluster analysis reveals that there are numerous major subjects in CSR research in the SME setting that are interconnected and can provide important insights for stakeholders in achieving sustainability and improved business performance. The findings show the trends that highlights the importance of SMEs in promoting sustainable development and the need for further research to guide the design of effective CSR strategies that can benefit both the environment and society